The Role of Safety Culture, Clinical Leadership Capacity, and Teamwork - Rika Rika; Hery Winoto Tj (Goodwood Publishing, 2026)
Purpose: This study aims to examine the effects of patient safety culture and clinical leadership capacity on nurses’ incident reporting compliance, with teamwork tested as a mediating mechanism. Research methodology: A census survey was conducted among 204 nurses at Sentra Medika Hospital Cikarang. Data were collected using a structured questionnaire comprising 18 validated indicators and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The results indicate that patient safety culture has a significant positive effect on both incident reporting compliance and teamwork. Clinical leadership capacity also demonstrates significant positive effects on teamwork and reporting compliance. Notably, teamwork shows a significant negative direct effect on incident reporting compliance, suggesting a preference for informal, team-based problem resolution that may substitute for formal reporting processes. However, teamwork significantly mediates the relationships between patient safety culture, clinical leadership capacity, and reporting compliance. Conclusions: The findings highlight a paradoxical role of teamwork in patient safety. While collaborative environments are essential, they must be strategically aligned with non-punitive and transparent reporting systems. Strengthening patient safety culture and clinical leadership, while institutionalizing team practices that reinforce formal reporting, is essential to enhance sustainable patient safety performance. Limitations: The study is limited to a specific hospital setting and may not be generalizable to all healthcare environments. Additionally, the study relies on self-reported data, which may introduce bias. Contributions: This study contributes to the understanding of how patient safety culture, clinical leadership capacity, and teamwork interact to influence incident reporting compliance in hospitals, emphasizing the need for a balanced approach that integrates both formal reporting systems and collaborative team practices.